Gut Microbiome-Centered Therapies for Alcohol-Associated Liver Disease - Ranjbarian, Tannaz; Schnabl, Bernd (Seminars in Liver Disease, 2023)
Globally, liver disease caused by alcohol is becoming more prevalent each year. Misuse of alcohol causes a spectrum of liver diseases, such as liver steatosis, steatohepatitis, fibrosis, cirrhosis, and hepatocellular carcinoma. The cornerstone of treatment is abstinence from alcohol. In spite of this, available treatment for alcohol-associated liver disease (ALD) shows limited effectiveness currently. There are numerous ways in which alcohol disrupts the gut–liver axis, including dysbiosis of the gut microbiome, disruption of mucus and epithelial cell barriers, impaired production of antimicrobial molecules, and dysfunction of the immune system, causing translocation of viable microbes and microbial products to the liver and systemic circulation. Microbial exposure results in not only inflammation and progression of liver disease but also infections in late-stage ALD. This led scientists to focus their therapeutic strategies and targets for ALD on the gut microbiome. Throughout this review, we address the role of gut microbiome–centered therapeutic approaches for ALD focusing predominantly on randomized controlled trials. We will summarize the latest clinical trials using probiotics, antibiotics, and fecal microbial transplants in modulating the gut–liver axis and for improvement of ALD.
Keywords: alcoholic liver disease; liver steatosis; hepatocellular carcinoma; microbiota